Comparative outcome analysis of hydroxychloroquine/chloroquine, remdesivir and standard of care treatment against COVID-19 infection - Kumar, Vikas; Mahato, Sumit Kumar (International Journal of Basic & Clinical Pharmacology, 2020)
This study aimed to compare the efficacy and safety of hydroxychloroquine/chloroquine (HCQ/CQ), remdesivir and standard of care treatment (SOC) in patients with nCoV-19 based on the RCTs available in the literature. We conducted a cumulative review of all the RCTs published for the treatment of nCoV-19. Analysis for odds of patient recovery on HCQ/CQ, remdesivir and SOC treatment was accomplished and recovery was expressed as undetectable viral RNA levels. Total sample size in our analysis was 978 from six RCTs, in which nCoV-19 positive patients treated with HCQ/CQ, remdesivir and SOC were 166,560 and 252, respectively. SOC treatment showed increase in 2-fold of patients’ recovery as compared to the HCQ/CQ group (p=0.0006). Further, patients reported 1.5-3-fold increase in adverse events in remdesivir and HCQ/CQ group as compared to SOC group (p=0.0016 and p<0.0001). Our finding suggests remdesivir or HCQ/CQ ensures no benefit over SOC treatment, which may be attributed to the adverse events exhibited by remdesivir, or inefficacy of HCQ/CQ.